Electrospun MnCo2O4/carbon-nanofibers as oxygen electrode for alkaline zinc-air batteries. (1st November 2022) - Alegre, C.; Busacca, C.; Di Blasi, A.; Cannilla, C.; Barbera, O.; Antonucci, V.; Lázaro, M.J.; Baglio, V.
Abstract: A MnCo2 O4 catalyst supported on nitrogen-doped carbon nanofibers (CNF) obtained in a single-step electrospinning process is presented. MnCo2 O4 /CNF is investigated as bifunctional electrode for the electrocatalysis of oxygen in metal-air batteries. Crystallographic structure, morphology, and surface properties are analyzed using solid-state characterization techniques that reveal the presence of a 20 nm-particle-sized spinel and a large amount of oxidized metal species (Mn 4+ and Co 3+ ). These features are correlated with the electrochemical behavior for the oxygen reduction (ORR) and oxygen evolution (OER), showing good performances in particular for the OER compared with IrO2, benchmark catalyst for this reaction. Results revealed a synergistic effect of the catalytically active nitrogen-doped carbon nanofiber and the manganese and cobalt active species from the spinel, being responsible for the remarkable reversibility of this catalyst (ΔE = 799 mV), outperforming most of the previous works in the literature on this type of manganese/cobalt-based spinel materials. A preliminary test of an alkaline Zn-air battery equipped with this catalyst at the oxygen (positive) electrode confirms proper activity and stability during cycling operations typical of these rechargeable devices. Besides, the spinel-nanofiber-based catalyst has been produced by an easily-scalable electrospinning process, representing an advance of the current technology on positive electrodes for metal-air batteries. The curated synthesis of our MnCo-N-CNF spinel is fundamental to obtaining a catalyst with a high intrinsic catalytic activity (determined by rotating disk electrode) and an appropriate performance in a relevant environment (both gas diffusion electrode and Zn-air battery). Highlights: A MnCo2 O4 supported on N-doped CNF is obtained in a single-step electrospinning process. MnCo2 O4 /CNF is investigated as bifunctional electrode for the electrocatalysis of oxygen. Remarkable reversibility (ΔE = 799 mV) and performance for the OER are recorded.